Brain catecholamine depletion and motor impairment in a Th knock-in mouse with type B tyrosine hydroxylase deficiency. (14th August 2015) - Korner, Germaine; Noain, Daniela; Ying, Ming; Hole, Magnus; Flydal, Marte I.; Scherer, Tanja; Allegri, Gabriella; Rassi, Anahita; Fingerhut, Ralph; Becu-Villalobos, Damasia; Pillai, Samyuktha; Wueest, Stephan; et al.
Abstract : Tyrosine hydroxylase catalyses the rate-limiting step in catecholamine synthesis. Korner et al. present a novel mouse model of tyrosine hydroxylase deficiency type B, which is associated with complex encephalopathy of perinatal onset. Characterization of the model provides insights into disease mechanisms, with implications for treatment. Abstract : Abstract : Tyrosine hydroxylase catalyses the hydroxylation of L-tyrosine to l -DOPA, the rate-limiting step in the synthesis of catecholamines. Mutations in the TH gene encoding tyrosine hydroxylase are associated with the autosomal recessive disorder tyrosine hydroxylase deficiency, which manifests phenotypes varying from infantile parkinsonism and DOPA-responsive dystonia, also termed type A, to complex encephalopathy with perinatal onset, termed type B. We generated homozygous Th knock-in mice with the mutation Th -p.R203H, equivalent to the most recurrent human mutation associated with type B tyrosine hydroxylase deficiency ( TH -p.R233H), often unresponsive to l -DOPA treatment. The Th knock-in mice showed normal survival and food intake, but hypotension, hypokinesia, reduced motor coordination, wide-based gate and catalepsy. This phenotype was associated with a gradual loss of central catecholamines and the serious manifestations of motor impairment presented diurnal fluctuation but did not improve with standard l -DOPA treatment. The mutant tyrosine hydroxylase enzyme was unstable and exhibited deficient stabilization by catecholamines, leading to decline of brain tyrosine hydroxylase-immunoreactivity in the Th knock-in mice. In fact the substantia nigra presented an almost normal level of mutant tyrosine hydroxylase protein but distinct absence of the enzyme was observed in the striatum, indicating a mutation-associated mislocalization of tyrosine hydroxylase in the nigrostriatal pathway. This hypomorphic mouse model thus provides understanding on pathomechanisms in type B tyrosine hydroxylase deficiency and a platform for the evaluation of novel therapeutics for movement disorders with loss of dopaminergic input to the striatum.